Chronic rhinosinusitis with nasal polyps impact in severe asthma patients: Evidences from the Severe Asthma Network Italy (SANI) registry. (May 2020) - Canonica, Giorgio Walter; Malvezzi, Luca; Blasi, Francesco; Paggiaro, Pierluigi; Mantero, Marco; Senna, Gianenrico; Heffler, Enrico; ,; Bonavia, M.; Caiaffa, P.; Calabrese, C.; Camiciottoli, G.; et al.
Abstract: Background: The clinical and laboratory features of patients enrolled in the Severe Asthma Network in Italy (SANI) registry, a web-based observatory collecting demographic, clinical, functional and inflammatory data of patients with severe asthma were evaluated, with a special emphasis to chronic rhinosinusitis with nasal polyposis (CRSwNP). Methods: For each eligible patients the following information has been collected: demographic data, clinical features, asthma control in the previous month according to the GINA (Global INitiative for Asthma) Guidelines and standardized questionnaires, concomitant regular and on demand treatments and inflammatory markers. Results: 695 patients with severe asthma enrolled in 66 SANI centers were analyzed. The prevalence of chronic rhinosinusitis with nasal polyposis was 40.6%. Atopic dermatitis and bronchiectasis was significantly more frequent in patients with CRSwNP than in subjects without nasal polyposis; similarly, FeNO values are significantly higher in subject with CRSwNP than in patients without nasal polyposis. Finally, patients with CRSwNP had a significantly higher number of asthma exacerbations per year, more days on oral corticosteroids and were more likely to be OCS long term users. Conclusion: OCS sparing is needed in patients with severe asthma, mainly in subjects with CRSwNP, adopting adequate strategies such as a better adherence to the treatment with inhaled therapy according to the GINA recommendations, the use of biologic agents and a multidisciplinary approach of the patient. Highlights: Nasal polyposis (CRSwNP) is frequent in patients with severe asthma (SA). Severe asthmatics with associated CRSwNP had higher annual exacerbations rate. Patients with SA and CRSwNP received more frequently oral corticosteroids (OCS). CRSwNP in SA patients expose them to high risk of OCS related adverse events.